Symbolic Meaning and Cultural Value in the Mappanre Temme Tradition in the Bugis-Makassar Community - Kartika Septiary Pratiwi Musa; Darwis Said; Alimuddin (Economics and Business Journal (ECBIS), 2026)
Indonesia is known as a country rich in local culture and traditions that are passed down from generation to generation. One of the traditions that is still preserved by the Bugis-Makassar people is Mappanre Temme, which is a procession of Qur'an khatam which is an important part of the traditional wedding series. This research aims to examine the symbolic meaning and cultural values in the Mappanre Temme tradition and its relevance in the life of modern society. The method used is a literature study with a qualitative descriptive approach. The results of the study show that this tradition contains religious, educational, social, and moral values. Apart from being a symbol of the spiritual readiness of the bride-to-be, this tradition is also a medium for the preservation of Islamic values and local culture. However, modernization also affects the meaning of this tradition, so sustainable preservation efforts are needed.